2007
DOI: 10.1002/ajmg.b.30526
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine beta‐hydroxylase (DBH) activity and ‐1021C/T polymorphism of DBH gene in combat‐related post‐traumatic stress disorder

Abstract: The roles of dopamine (DA) and norepinephrine (NE) in posttraumatic stress disorder (PTSD) are unclear. The aim of the study was to determine plasma dopamine beta-hydroxylase (DBH) activity and DBH-1021C/T gene polymorphism in combat veterans with (N = 133) or without (N = 34) chronic PTSD. Similar frequencies in genotype or allele distribution were found between veterans with or without PTSD. War veterans with PTSD had lower DBH activity, associated with the DBH-1021C/T variant in DBH genes, than veterans wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 19 publications
2
49
1
1
Order By: Relevance
“…11, 1416 The profound effect of these SNPs on circulating DBH levels is supported by their large effect on mRNA expression in liver and lung. We extrapolate from these results that genetic effects likely occur in all sympathetically innervated organs and thereby affect serum DBH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11, 1416 The profound effect of these SNPs on circulating DBH levels is supported by their large effect on mRNA expression in liver and lung. We extrapolate from these results that genetic effects likely occur in all sympathetically innervated organs and thereby affect serum DBH.…”
Section: Discussionmentioning
confidence: 99%
“…Significant inter-individual variability in plasma DBH levels has been associated with genetic DBH variants. The minor allele ( T ) of the promoter single nucleotide polymorphism (SNP) rs1611115 (−1021C/T) is associated with lower serum DBH levels, accounting for 35–52% of the variation across populations, 11, 1416 while individuals homozygous for the C allele have increased plasma norepinephrine levels. 19 However, it remains unknown how rs1611115- T reduces circulating DBH and norepinephrine levels.…”
Section: Introductionmentioning
confidence: 99%
“…Lower plasma DBH activity has been reported in different psychopathological disorders [59]. Although evidence suggests a hyperactive SAM system in patients with PTSD [60,61,62,63], Mustapic et al [64] reported lower DBH activity in war veterans with PTSD compared to war veterans without PTSD, indicating that those who exhibited lower plasma DBH activity after a traumatic event were less resilient and more vulnerable to developing PTSD. This finding is consistent with the decrease in catecholamine levels observed on day 24 in the passive subjects.…”
Section: Discussionmentioning
confidence: 99%
“…This reasoning has led to several studies examining gene variants in the CRH gene [18], the glucocorticoid receptor (GR) gene [19], and in FKBP5 [20,21], a gene which regulates cortisol-binding affinity and nuclear translocation of GRs. Because the dopaminergic and adrenergic systems are also implicated in stress and fear biology, variation in dopamine regulating genes (e.g., dopamine β-hydroxylase, dopamine transporter and DRD2 genes) has been investigated in association with PTSD [22][23][24][25][26][27][28]. Variation in the serotonin transporter gene has been widely studied in association with PTSD [29][30][31] and in particular in the context of gene by environment studies [32][33][34] (see below for further discussion of this type of design).…”
Section: Gene Association Studies In Ptsdmentioning
confidence: 99%